De novo brain AVM following radiotherapy for cerebral cavernous malformation in a child: A 15-year clinical course. Issue 4 (August 2022) - Matsoukas, Stavros; Bageac, Devin V; DeLeacy, Reade; Berenstein, Alejandro; Fifi, Johanna T
Multiple de novo brain arteriovenous malformations (bAVM) have been reported in the literature, raising questions about the contended purely congenital nature of these lesions. We present the 15-year course of a pediatric patient, who initially presented at age 5 with a thalamic cavernous malformation and was treated with radiosurgery, and then subsequently developed a thalamic de novo bAVM immediately adjacent to the initial lesion location, discovered 2 years later. Treatment of the bAVM entailed two transarterial embolizations and one radiosurgery session which ultimately led to complete angiographic resolution. Finally, this patient's course was complicated by intraparenchymal hemorrhage and acute obstructive hydrocephalus, and further imaging revealed two newly formed cavernous malformations, also associated with the initial lesion's location, that have remained stable since their formation. This case likely represents the second-hit model for the formation of vascular malformations, as sparsely supported by the current literature. According to this, genetically aberrant, yet quiescent, brain areas might promote the de novo formation of vascular malformations after brain injury, including radiation.